Building Digital Justice: Reinterpreting Ḥifẓ al-ʿIrḍ in Personal Data Protection and Legal Aid for Data Breach Victims in Indonesia - Ika Pusparini Anindita Jayasinga; Agus Triono; Muhammad Akib; Elfa Murdiana; Muhimmatul Mukaromah (Justicia Islamica, 2026)
This article examines the systemic failure of personal data protection in Indonesia as an issue that goes beyond technical and regulatory shortcomings and touches the very core of human dignity. Although Law No. 27 of 2022 on Personal Data Protection has provided normative consolidation, the legal ecosystem underpinning it remains fragile: a non-independent supervisory body, structurally weak enforcement mechanisms, and systemic inequities in access to justice render data subjects' rights illusory. This article employs a normative-empirical method with three complementary approaches: the legal philosophy approach is used to deconstruct the paradigmatic assumptions underpinning the data protection regime and reconstruct it on the foundation of human dignity; the conceptual approach is used to redefine ʿirḍ from social reputation toward digital identity and data sovereignty; and the maqāṣid al-sharīa approach within Jasser Auda’s framework is used to assess the normative adequacy of the existing regime and to construct an argument that data protection must be classified as ḍarūriyyāt—a primary necessity—because its violation simultaneously threatens ḥifẓ al-nafs, ḥifẓ al-ʿaql, ḥifẓ al-māl, and ḥifẓ al-ʿirḍ. Based on these findings, this article proposes a Maqasid-Oriented Legal Aid (MOLA) model that operates across three dimensions: restorative, preventive-structural, and community-based accessibility. The main contribution of this article is the redefinition of data protection as an active and affirmative mandate of ḥifẓ al-ʿirḍ, while also offering a framework for legal aid that is normatively robust and institutionally realistic in the Indonesian context.